Oral changes in preterm children (Research, Society and Development, 2022)
Prematurity and low birth weight are frequent situations, and its impact on the development of the baby's stomatognathic system has been studied. The most common oral alterations are enamel defects, delayed eruption of the deciduous dentition and dental caries. In this sense, the proposal of this study was to carry out a review of the literature emphasizing the oral alterations in preterm infants, the importance of the knowledge for the appropriate treatment and follow-up of the patients. Articles from 1984 and 2018 were selected using the following databases: PubMed, Google academic, Scielo, Brazilian Bibliography of Dentistry (BBO), Lilacs, Medline, as well as websites, technical books and national and international publications. The most common oral alterations in preterm infants are dental defects, alterations in chronology of eruption, and a predisposition to develop tooth decay. Therefore, it is important to carry out early preventive care targeted to these children to avoid future harm. Knowledge and care with preterm oral changes favors the adequate growth and development of the stomatognathic system, as well as preventing and reducing possible dental changes.